PUBLIC SERVICE AND COMMUNITY SATISFACTION AT THE COUNTY JAIL OF THE COUNTY JAIL - Asmiranda, Asmiranda; Sulmiah, Sulmiah; Yamin, Muh Nur (Universitas Negeri Makassar, 2025)
This study aims to determine the quality of service and community satisfaction as well as the relationship between service quality and community satisfaction at the Sabutung Health Center, Pangkep Regency. This study uses study tools from Zeithaml, namely regarding physical appearance (tangibles), reliability (realibilitty), responsiveness (responsiveness), assurance (assurance), care (empathy). While community satisfaction uses tools from the study of Fandy Tjiptono and Chandra stating that patient satisfaction can be seen from feelings of pleasure or disappointment with the services provided by service providers that refer to service quality. This study uses a quantitative approach with a type of correlational research research which is research to determine and find out whether there is a relationship between variables. Sample withdrawal using simple random sampling technique. Data collection is done by field observation techniques, distributing questionnaires, interviews and documentation. The data analysis technique used is descriptive statistical analysis, simple correlation to explain the relationship between two variables The results of the research show that the quality of service at the Sabutung Community Health Center, Pangkep Regency is included in the adequate category. Meanwhile, community satisfaction at the Sabutung Community Health Center, Pangkep Regency is also in the sufficient category. And based on the research results, it was concluded that service quality and community satisfaction at the Sabutung Community Health Center, Pangkep Regency had a significant, strong and positive relationship with a percentage of 67,7%.